Contribution to the knowledge of the caddisfly fauna of Algeria: An updated checklist of Algerian Trichoptera with new records from the Aures region - Dambri, Besma M.; Karaouzas, Ioannis; Samraoui, Boudjéma; Samraoui, Farrah (Zootaxa, 2020)
The caddisfly fauna of Algeria is poorly known and the few sporadic studies available were carried out decades ago. In this study, caddisfly larvae, pupae, and adults were collected in 11 stream localities from the Aures region, northeastern Algeria. Caddisflies were regularly sampled between April 2018 and February 2020. Two genera are new records to Algeria: Plectrocnemia and Setodes. In addition, four Trichoptera species are new to the Algerian fauna: Tinodes dives, Hydropsyche modesta, Plectrocnemia conspersa and Setodes acutus. Future caddisfly surveys in the region will doubtlessly contribute significantly to the incompletely known Trichoptera fauna of Algeria.